The effect of distance between childcare centre and residence on maternal labour market outcomes - Chan, Qi Yu (Nanyang Technological University, 2022)
In studying the effect of geographical proximity to childcare on mothers’ employment, past research had found mixed results and typically did not attempt to address potential endogeneity problems. Our study adopts an instrumental variable (IV) approach in examining the effect of distance between childcare centres and mothers’ residence on maternal labour market outcomes in Singapore. A proportionate stratified random sample of 400 married mothers aged 21 to 40 from middle-income households were recruited outside childcare centres. Child’s birth month was used to instrument distance and instrument relevance was established with a significant first-stage effect. Three maternal labour market outcomes were studied – hourly income, monthly income and employment. Results from regression analyses found significant distance effects on mothers’ income and likelihood of full-time employment. On average, staying 1km further away from the childcare reduces likelihood of full-time employment by 43% and hourly income by 52% (marginally significant), ceteris paribus. It also reduces mothers’ likelihood of earning within a higher monthly income bracket, broken down into a 50% increased likelihood of not earning an income (i.e., unemployed or housewife), and a 40% (marginally significant) increased likelihood of earning slightly below the median income in Singapore ($3,000 to $3,999). These findings support our policy recommendations to expand infant care services near mothers’ homes and incentivise employment and reskilling of mothers with career breaks. Future studies could validate our findings using a stronger identification strategy, and additionally explore distance effects between centres and mothers’ workplaces.